Children for Social Justice - McCrossin, Jeff (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2012)
It is often assumed that children lack the developed capacity to understand complicated political issues (for example, Arendt, 1959; Pearce, 2011; and Warmington, 2012a, 2012b). This assumption is contested through a review of the literature examining adult conceptions the child, and children’s rights to political participation, citizenship, and direct representation (Steffler, 2009; Wall & Dar, 2011; Wyness, Harrison, & Buchanan, 2004). A variety of historical and contemporary examples of children engaging in social justice campaigns and movements are provided (Elshtain, 1996; Milstein, 2010; Smith, 2012; Traubman, 2005; Bergmar, 2010). A potential means for supporting children in social justice engagement is explored through social justice education (Dover, 2009; Kelly & Brooks, 2009).